2021
DOI: 10.1186/s12933-021-01380-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of canagliflozin on NT-proBNP stratified by left ventricular diastolic function in patients with type 2 diabetes and chronic heart failure: a sub analysis of the CANDLE trial

Abstract: Background Identification of the effective subtypes of treatment for heart failure (HF) is an essential topic for optimizing treatment of the disorder. We hypothesized that the beneficial effect of SGLT2 inhibitors (SGLT2i) on the levels of N-terminal pro-brain natriuretic peptide (NT-proBNP) might depend on baseline diastolic function. To elucidate the effects of SGLT2i in type 2 diabetes mellitus (T2DM) and chronic HF we investigated, as a post-hoc sub-study of the CANDLE trial, the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The protective effects were attributed to several mechanisms, including the diuretic effect of SGLT2i, more efficient production of ATP, and mitochondrial function reestablishment [ 27 29 ]. The effect of SGLT2i on NT-proBNP was also recognized as another potential pathway to produce a beneficial impact [ 30 , 31 ] but remains controversial [ 32 ]. Our current results provide robust evidence that the association between NT-proBNP and mortality was more remarkable in HF patients with DM than without, suggesting that lowering NT-proBNP levels in patients with HF and DM would be a promising direction to gain benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects were attributed to several mechanisms, including the diuretic effect of SGLT2i, more efficient production of ATP, and mitochondrial function reestablishment [ 27 29 ]. The effect of SGLT2i on NT-proBNP was also recognized as another potential pathway to produce a beneficial impact [ 30 , 31 ] but remains controversial [ 32 ]. Our current results provide robust evidence that the association between NT-proBNP and mortality was more remarkable in HF patients with DM than without, suggesting that lowering NT-proBNP levels in patients with HF and DM would be a promising direction to gain benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of CV-related events in people with T2D and CV risk can be attributed in parts to the lowered NT-proBNP concentration in the canagliflozin arm of the CANVAS trial [ 134 ]. Also, a trend towards lower NT-proBNP levels in the subgroup with a lower LV diastolic function was observed in the canagliflozin treated group compared to the glimepiride treated arm, as shown in a sub-analysis of the CANDLE trial [ 135 ]. In line with canagliflozin, dapagliflozin also lowered NT-proBNP levels significantly more than placebo in the DAPA-HF cohort [ 124 ].…”
Section: Detection Of Heart Failure In Diabetesmentioning
confidence: 93%
“…The decreased NT-proBNP concentration in the canagliflozin arm of the CANVAS trial can be ascribed in part to the reduction in CV-related events in patients with T2D and CV risk [154]. In addition, a sub-analysis of the CANDLE study found a tendency toward decreased NT-proBNP levels in the subgroup with lower LV diastolic function in the canagliflozin treated arm compared to the glimepiride treated arm [155]. Dapagliflozin, like canagliflozin, reduced NT-proBNP levels considerably higher than placebo in the DAPA-HF group [145,149].…”
Section: Therapeutic Considerations Of Hf In Diabetesmentioning
confidence: 99%